HUBUNGAN LAMA DUDUK TERHADAP PENGGUNA KOMPUTER DENGAN SHOULDER PAIN PADA KARYAWAN PT.INSANI MEDICAL CENTER - Sonia Januarizky (2022)
Office workers who require employees to sit in front of the computer for a long time can cause disruption of physical activity behavior. Due to low physical activity will increase shoulder pain, many people can reduce flexibility and muscle strength as a result of apparent muscle fatigue. This is caused by a reduction in flexibility and muscle strength so that it is easier to experience muscle fatigue. A long working period can increase the occurrence of shoulder injuries, because it can overload the shoulder muscles to work excessively for a long time so that it will cause musculoskeletal problems. Objective: This study aims to determine the relationship between long sitting and computer users at PT. Insani Medical Center. Methods: This study used a cross sectional approach. A total of 50 employees of PT. Insani Medical Center participated in this study. This research instrument uses a long sitting questionnaire to determine the duration of the respondent's sitting at work, and a Shoulder Pain Disability Index questionnaire to assess the level of shoulder pain. . Results: Based on the results of data processing using SPSS 25.0, 10% respondents complained of mild pain and 90% respondents experienced moderate pain. After the correlation test was carried out, the correlation coefficient of Spearman's Rho sitting and shoulder pain was obtained p = -.305 with a significant value of p = 0.03. Conclusion: The conclusion in this study is that there is a significant relationship between the duration of sitting with complaints of shoulder pain.